Analysis and Design of Accounting Information Systems in order to Improve Internal Controls In Non Small Business (Micro Business Charity Muhammadiyah) In Region Tegal. - ., Mulyanto (PERMANA, 2013)
The purpose of this study was to determine the accounting information system implemented by the company and the extent to which the role of accounting information systems for managers in making decisions. The data analyzed were a) the company's accounting system implemented, b) the conditions and operations, c) method of accounting system d) the elements of the accounting system. From the data it is expected that researchers know the ratio of enterprise accounting system implemented with existing theory, as it makes the design of the accounting system adapted to the condition of the company. The results of this study are the internal control system implemented by BMT can be said is still weak, because it is in the execution of his duties there are sections that hold multiple functions. Thus, one element of the system as a means of monitoring internal pengndalian still less fulfilled. The dual task lies in the provision of credit is the part that does the payment and administration. BMT is still not implement good accounting information system, it can be seen from the use of the form is still inadequate. Form or document already qualified but still there are many forms or documents that have not been used properly. Thus the form or document is not helpful to create a good information system. As one example of the inadequate forms or documents needed in the system of credit is not the presence of the card that functions the same as the identity card. Keywords: analysis, accounting information system